Pedagogical Fundamentals of Game Activity in Preschool Children - Botirova Zuhrakhon Abdurahimovna; Mamajonova Nigorakhon Umidjon kizi (Zien Journals, 2023)
The article describes the role of family and society in child education, the role of play in the development of play activities of preschool children, and the role of play in the process of education.
Keywords: Team; game types; action games; didactic games